Biliary stent placement specialities in endoscipic treatment of common bile duct stones - M. A. Abzhalov; V. V. Yurchenko (Кубанский научный медицинский вестник)
The article is devoted to palliative treatment of mechanical jaundice, caused choledocholitiasis, get having patients with high operating risk and hemostasissystemdisturbances, by means for endobiliary stenting. Authors have researched reasons of efficacy decreasing and suggested original ways to elaborate that, after that have carried outcomparing the results in the groupofcomparison.